The pharmacokinetics of racemic MDPV and its (R) and (S) enantiomers in female and male rats. (1st October 2017) - Hambuchen, Michael D.; Hendrickson, Howard P.; Gunnell, Melinda G.; McClenahan, Samantha J.; Ewing, Laura E.; Gibson, Dillon M.; Berquist, Michael D.; Owens, S. Michael
Highlights: First report of sex-dependent ( R, S )-methylenedioxypyrovalerone (MDPV) and enantiomer differences in pharmacokinetics (PK). Males had significantly greater (p < 0.05) Intraperitoneal (ip) ( S )- and ( R, S )-MDPV bioavailability. Most significant PK differences were in the volume of distribution (Vdss or Vd). Sex differences in volume of distribution could be due to MDPV protein binding. There was no evidence of in vivo inversion of ( R )-MDPV or ( S )-MDPV to its antipode. Abstract: Background: These studies investigated the serum pharmacokinetic (PK) profile of racemic (3, 4)-methylenedioxypyrovalerone [( R, S )-MDPV)] and its ( R )- and ( S )-enantiomers in female and male Sprague Dawley rats. Methods: Intravenous ( R, S )-MDPV (3 and 5.6 mg/kg) and single enantiomer of ( R )- and ( S )-MDPV (1.5 mg/kg) were administered to both sexes for PK studies. Intraperitoneal (ip) bioavailability was determined at 3 mg/kg ( R, S )-MDPV. Locomotor activity studies were conducted after ip treatment with saline and 0.3-5.6 mg/kg of ( R, S )-MDPV. Results: PK values after iv ( R, S )-MDPV showed a significant ( p <  0.05) sex-dependent differences in the volume of distribution at steady state (Vdss ) for ( R )- and ( R, S )-MDPV at both ( R, S )-MDPV doses. The female S/R enantiomeric ratios for area under the concentration time curve (AUCinf ) and clearance were significantly lower and higher, respectively, than values determined in males. Importantly, there was no evidence of in vivo inversion of ( R )-MDPV or ( S )-MDPV to its antipode. There were, however, significant sex-dependent differences in volume of distribution after administration of the ( R )-enantiomer. Bioavailability studies of ip ( R, S )-MDPV showed greater variability and significantly greater bioavailability in male rats. Accordingly, there was a significantly greater maximal distance traveled measurement in male rats at a 3.0 mg/kg dose. Conclusion: PK sex differences in ( R, S )-MDPV and enantiomers were most apparent in volume of distribution, which could be caused by differences in drug blood and tissue protein binding. The increased magnitude and variance in ip bioavailability in male compared to female rats could lead to sex-dependent differences in the pharmacological action caused by active enantiomer ( S )-MDPV.